Pig liver sectorization and segmentation and virtual reality depiction - Zanchet,Dinamar José (2002)
OBJECTIVE: To determine pig liver sectorization and segmentation through the representation of their correlation to portal and hepatic veins, and through the development of virtual reality (VR) animation. METHODS: Twenty models were obtained by injection of portal and hepatic veins from Landrace pig livers with a methyl methacrylate solution, and by corrosion of the hepatic parenchyma with chloride acid 35%. VR animation of one of these models was conducted through graphic software (3D Studio Max 3.0). RESULTS: Constant presence of eight segments and six venous drainage sectors was observed. Pig portal vein bifurcation was not noticed. Hepatic veins were named according to their embryological origin. Correlation between venous system and hepatic parenchyma was established by means of VR animation. CONCLUSION: These models facilitated both the study of pig hepatic sectors and segments, and the proposal of hepatic veins nomenclature. These models have also been used for the development of VR animated models which show the correlation between the hepatic parenchyma and the pig liver venous system as well as the observation of them from several points of view.